2021
DOI: 10.48550/arxiv.2103.16396
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular Interactions Induced by a Static Electric Field in Quantum Mechanics and Quantum Electrodynamics

Mohammad Reza Karimpour,
Dmitry V. Fedorov,
Alexandre Tkatchenko

Abstract: We study the interaction between two neutral atoms or molecules subject to a uniform static electric field, using quantum mechanics (QM) and quantum electrodynamics (QED) applied to coupled harmonic Drude oscillators. Our focus is to understand the interplay between dispersion interactions and field-induced electrostatics and polarization in both retarded and non-retarded regimes. We present an exact solution for two coupled oscillators using QM and Rayleigh-Schrödinger perturbation theory, demonstrating that … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…[48] for a simple argument). Hence, we may comfortably neglect any effect of E 0 in the dispersive interaction [50,51].…”
Section: A Dispersive Forcementioning
confidence: 99%
See 1 more Smart Citation
“…[48] for a simple argument). Hence, we may comfortably neglect any effect of E 0 in the dispersive interaction [50,51].…”
Section: A Dispersive Forcementioning
confidence: 99%
“…It was recently shown that an electrostatic field could generate a repulsive interaction between atoms [47]. The interpretation of their result was disputed [48,49], and subsequently, a thorough and rigorous study was carried out to settle the issue [50,51]. However, regardless of the interpretation, Ref.…”
Section: Introductionmentioning
confidence: 99%